Optimisation of polymer particles propulsion on caesium ion-exchanged channel waveguide for stem cells sorting applications - Mukhzeer, Mohamad Shahimin; O. G., Hellesø; J. S., Wilkinson; T., Melvin (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis on June 20th - 22nd, 2009, at MS Garden Hotel, Kuantan, Pahang, Malaysia.